A novel active deep-sea low-damage pressure-retaining organisms sampler - Liu, Guangping; Jin, Yongping; Peng, Youduo; Liu, Deshun; Wan, Buyan (Frontiers in Marine Science, 2022)
Capturing less damaged organisms samples is the basis for research on the biological communities, living environments, biological life compositions, and biological tissue structures of organisms livinin the deep seabed. The hadal snailfish is pressure-tolerant, cold-tolerant, and easily damaged. This research used a hydraulic suction macro-biological pressure-retaining sampler (HSMPS) to capture less damaged hadal snailfish samples via pumping. As the hadal snailfish is sucked into the macro-organism pressure-maintaining sampler, it inevitably collides with the suction pipe in the diversion area (SPDA) and the inner wall of the pressure-maintaining cylinder in the pressure-maintaining area (PCPA). Therefore, a finite element analysis model of a hadal snailfish with a real geometric shape was constructed by obtaining the material mechanical properties of different parts of the fish on the seabed through static compression tests, and the dynamic modeling and response analysis of the hadal snailfish during the capture process was carried out. Moreover, the dynamic response changes of the stress, strain and acceleration of various tissues and organs of the hadal snailfish during the capture process were determined, thereby providing technical support for the research and development of marine biological sampling equipment.